Evasão no ensino superior no curso de ciências biológicas do Instituto Federal de Educação, Ciência e Tecnologia do Amapá – IFAP – Campus Laranjal do Jari entre 2014 – 2018 - SILVA, Francisca Leiliane Rego da (Instituto Federal do Amapá, 2021)
The present research aims to analyze the causes of evasion in higher education in the course of Biological Sciences of the Federal Institute of Education, Science and Technology of Amapá (IFAP) - Campus Laranjal do Jari between 2014 - 2018. It is a methodological bias study of a predominantly qualitative approach, having as an instrument of data collection the documentary analysis and narrative interview, in which the interview will be applied only to the students who have escaped from the course, encompassing the five Bachelor's degrees in Biological Sciences. The results obtained allow us to analyze the causes of avoidance and the real motives behind the decision making that led to the abandonment of the course. It is con-cluded that the main reasons are justified in the work / study relationship; change of course; identification; equivocation in the choice, being these, with greater index of occurrence, be-sides others, like affinity; trip; health problem; approval in competition; pregnancy, these, with lower incidence rate. Therefore, it is necessary that the educational institution work with the elaboration of continuous strategies that improve the development of learning and ensure the permanence of these students in the classroom with flexible methodologies, taking into account the historical context of the student, is an integral part of both courses, institution and teaching and learning. However, it is expected that this work contributes to the school com-munity, especially those who believe in quality education and that promotes public policies that will eradicate or minimize such evasion within schools as a whole, providing subsidies for other educational research.